2010
DOI: 10.1007/s00531-010-0600-8
|View full text |Cite
|
Sign up to set email alerts
|

A 3-D lithospheric model of the Caribbean-South American plate boundary

Abstract: A 3-D structural model of the Caribbean-South American plate boundary was constructed by gravity modeling. The model was constrained by four wide-angle seismic refraction sections, Moho depth estimations from receiver functions, and additionally seismological hypocenters, surface geology, and geodynamic information. Density values were calculated from empirical velocitydensity functions, and mineralogical-chemical composition considering specific P/T conditions. We tested different structural models for Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 46 publications
3
18
0
Order By: Relevance
“…Figure 8 show that there are significant differences among Moho values estimated with spectral analysis and Moho estimated with receiver function. On the other hand, Moho depth values in Figure 7 and closely match the values estimated by Schmitz et al [38] and also produces the best fits to the observed Bouguer gravity data [54]. According to Schmitz et al [38] the mismatch between seismic Moho and receiver function Moho is caused by the resolution of these technics.…”
Section: Effective Elastic Thickness and Mohosupporting
confidence: 83%
See 1 more Smart Citation
“…Figure 8 show that there are significant differences among Moho values estimated with spectral analysis and Moho estimated with receiver function. On the other hand, Moho depth values in Figure 7 and closely match the values estimated by Schmitz et al [38] and also produces the best fits to the observed Bouguer gravity data [54]. According to Schmitz et al [38] the mismatch between seismic Moho and receiver function Moho is caused by the resolution of these technics.…”
Section: Effective Elastic Thickness and Mohosupporting
confidence: 83%
“…This pronounced negative Bouguer gravity anomaly has been studied by several authors [3,[51][52][53][54]. The negative gravity anomaly is roughly parallel to the arc platform extension, but it does not extend west of Gulf of Paria.…”
Section: Regional and Residual Gravity Anomalies And Their Correlatiomentioning
confidence: 70%
“…Subsequently the densities of these objects are calculated using one of the velocity-density relationships or through a trial and error approach. After that, the forward signal associated with these objects is compared with the measured gravity (e.g., Sanchez et al, 2011). A following step can be applying inversion approaches to reduce the misfit between the calculated and the measured gravity (e.g., Ebbing et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A following step can be applying inversion approaches to reduce the misfit between the calculated and the measured gravity (e.g., Ebbing et al, 2001). This gravity modelling object-based approach has been done without a standardized methodology on how to extract the subsurface structures from 3D subsurface data, and has traditionally mainly been based on the user experience or pre-existing data (e.g., Ebbing et al, 2001;Sanchez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For a single geophysical technique, e.g., seismic reflection/refraction or tomography, the interpretation and the classification have been done without a standardized methodology and were often done based on contouring or expert interpretation of the 3D seismic velocity data cube and a priori information about the studied area (e.g., Ebbing et al (2001), Li (2010) and Sanchez et al (2011)). However, this can be sensitive to subjective choices that can often make the process unrepeatable.…”
Section: Introductionmentioning
confidence: 99%